Cytomorphological Spectrum of Thyroiditis: A Review of 110 Cases. (1st March 2018) - Chandanwale, Shirish S.; Nair, Rahul; Gambhir, Anushree; Kaur, Supreet; Pandey, Aditi; Shetty, Abhinav; Naragude, Piyusha
Abstract : Introduction . Different types of thyroiditis may share some parallel clinical and biochemical features. Timely intervention can significantly reduce morbidity and mortality. Aim . Aim of this study is to find the frequency of various thyroiditis, study the cytomorphological features and correlate with clinical findings including radiological findings, thyroid function test, and anti-thyroid peroxidase antibodies (Anti-TPO antibodies). Materials and Methods . The study included consecutive 110 cases of thyroiditis. Detailed cytomorphological features were studied and correlated with ultrasonography findings, thyroid function test, anti-thyroid peroxidase antibodies (anti-TPO) and histopathological features where thyroidectomy specimens were received for histopathological examination. Results . The majority were Hashimoto's thyroiditis (n = 100 ) and females (n = 103 ). Other forms of thyroiditis were Hashimoto's thyroiditis with colloid goiter (n = 5 ), De Quervain's thyroiditis (n = 3 ), and one case each of postpartum thyroiditis and Hashimoto's thyroiditis with associated malignancy. The majority of patients were in the age group of 21–40 (n = 70 ) and the majority (n = 73 ) had diffuse enlargement of thyroid. The majority of patients were hypothyroid (n = 52 ). The serum anti-TPO antibodies were elevated in 47 patients out of 71 patients. In the 48 patients who underwent ultrasonography, 38 were diagnosed as having thyroiditis. The most consistent cytomorphological features seen in fine-needle aspiration smears of Hashimoto's thyroiditis were increased background lymphocytes, lymphocytic infiltration of thyroid follicular cell clusters, and Hurthle cells. Conclusion . The diagnostic cytological features in Hashimoto's thyroiditis are increased background lymphocytes, lymphocytic infiltration of thyroid follicular cell clusters, and Hurthle cells. FNAC remains the "Gold Standard" for diagnosing Hashimoto's thyroiditis. Clinical history, thyroid function, and biochemical parameters are the key for diagnosis of other forms of thyroiditis.